Determinants of Earnings Quality With the Company's Life Cycle, and Related Party Transactions and the Implications on Firm Value - Kurnia, Anita; Apollo Daito (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study aims to prove the empirical effect of the company's life cycle, and related party transactions on earnings quality and its implications toward firm value. This study uses a sample of the mining sector listed on the Indonesia Stock Exchange for the period 2015 – 2020. The sample in this study consisted of 12 companies. Sampling using purposive sampling method and is a quantitative research with panel data regression model.The results show that the company life cycle and related party transactions have a significant positive effect on earnings quality and a significant negative effect on firm value, earnings quality has a significant positive effect on firm value, earnings quality mediates between the firm's life cycle and firm value, and earnings quality does not mediate between related party transactions and firm value.